PERUBAHAN PELAYANAN KELUARGA BERENCANA PADA MASA PANDEMI COVID-19 - Yunifitri, Astri; Butarbutar, Jorgis (Zona Kebidanan: Program Studi Kebidanan Universitas Batam, 2021)
The Covid-19 pandemic has had a major impact on the implementation of the Family Be (KB) program which has relied on face-to-face activities in socializing, counseling, and providing services. The decline in access to health facilities during the pandemic has resulted in a decrease in the number of family planning programs and the number of contraceptive users, which can lead to unwanted and untimely pregnancies. This increases the risk of an increase in the number of unplanned pregnancies and a population explosion that has an impact on the higher Maternal Mortality Rate (MMR) and thwarts efforts to build Indonesia's future with quality resources in the bonus era. This study aims to determine the planning and evaluation of family planning programs during the Covid-19 pandemic. This research method uses a library research approach with a literature study approach. From the results of the study, it is known that the family planning program that was run during the pandemic had implemented planning based on the priority of existing problems by refocusing funds, issuing family planning service program guidelines during the pandemic, and maximizing the role of family planning instructors to assist services. Monitoring and supervision have also been carried out on a regular basis. However, there is a need for support in family planning services by providing contraception devices and complete health protocol PPE evenly, increasing the involvement of cadres and the community for areas that do not have easy access to services and there is no vaccine that is absolutely safe to use for pregnant and lactating women.